Da camisa de força ao psicotrópico: um olhar hermenêutico existencial para o sofrimento no contexto da atenção primária à saúde. - Oliveira, Ana Paula Galdino de (2020)
The high use of psychotropics, especially anxiolytics and antidepressants, in recent decades, signals the increase in psychic disorders, making this reality a serious public health issue: the medicalization of psychological suffering. Bringing the Basic Health Unit as a setting / field, the research aimed to understand the resonances of the use of psychotropic drugs in the ways of caring for the suffering of women in the context of primary health care. With that, the experiences narrated by six women users of a service were collected through the realization of two Creativity Workshops. In addition, narratives recorded in Logbooks of the researcher's experience / narrative were produced. The interpretation of the narrated experiences followed the analytics of Heidegger's existence with Hans-George Gadamer's Philosophical Hermeneutics, following a set of meanings that takes shelter in language, and that puts us in a different direction, contrary to the reductionist dictates of modern scientific production . The approximation with the narratives makes us question the main policies, such as the Humanization of health, in the face of the denunciations announced in the narratives, from cries for help for the helplessness in the condition of care offered, demonstrating the noises and paradoxes of a service (system ) providing the condition of dependence on the drug, leaving the existential demand “shown” in the narrated suffering unheard.